Gentle Breeze of Digitalization Blowing in the Urban Lifestyle: A Case Study of Bangladesh (Global Journal of Management and Business Research, 2015)
The aim of this study is to observe the current state of ICT (information and communications technology) in the urban areas of Bangladesh as well as make some recommendations for the shortcomings of e service in urban areas in Bangladesh. Data were collected from the various journals of Bangladesh government as well as English newspapers, although the study is mainly descriptive in nature. The study finds that Bangladesh has made progress in the urban lifestyle regarding Computer training, e-Insurance , Banking facilities, Payment of rural electricity bill facility, Health services, Creation of jobs, Union digital center Blog, District e- service center #x2013;settlement record, National e-service system (NESS),Life and earning oriented national e-information book having life and earning oriented data, Mobile Key-pad and the opening of SMS in Bangla, My alphabet, National portal framework and website, Multimedia class room and digital summary,E #x2013;book ,online application management of non govt.
Keywords: ICT (information and communications technology); union digital center; payment of rural electricity bill facility; district e- service center #x2013; settl